Reduced colonic mucin degradation in breastfed infants colonized by Bifidobacterium longum subsp. infantis EVC001. Issue 10 (17th September 2018) - Karav, Sercan; Casaburi, Giorgio; Frese, Steven A.
Abstract : Mucin glycoproteins play an important role in protecting the gut epithelium by keeping gut microbes from direct contact with the gut epithelium while allowing for diffusion of small molecules from the lumen to the epithelium. The mucin glycocalyx can be degraded by gut bacteria such as Bacteroides and Akkermansia, but other bacteria, such as Bifidobacterium longum subsp . Infantis, cannot consume mucin glycans. Untargeted mass spectrometry profiles were compared to microbiome profiles to assess how different gut microbiomes affect colonic mucin degradation. Samples obtained from nine infants colonized by Bifidobacterium infantis EVC001 and from 10 infants colonized by higher levels of mucolytic taxa (controls), including Bacteroides, were compared. Previously performed untargeted nano‐high‐performance liquid chromatography‐chip/time‐of‐flight mass spectrometry was used to detect and quantify glycans originating from colonic mucin. Colonic mucin‐derived O ‐glycans from control infants composed 37.68% (± 3.14% SD) of the total glycan structure pool, whereas colonic mucin‐derived O ‐glycans made up of only 1.78% (± 0.038% SD) of the total in B. infantis EVC001 samples. The relative abundance of these colonic mucin‐derived O ‐glycans in the total glycan pool was higher among control, 26.98% (± 8.48% SD), relative to B. infantis‐ colonized infants, 1.68% (± 1.12% SD). Key taxa, such as Bacteroidaceae, were significantly and positively correlated with the abundance of these structures, while Bifidobacteriaceae were significantly and negatively associated with these structures. These results suggest that colonization of infants by B. infantis may diminish colonic glycan degradation and help maintain barrier function in the gastrointestinal tract of infants. Abstract : Mucin glycoproteins play an important role in protecting the gut epithelium. The mucin glycocalyx can be degraded by certain gut bacteria, such as Bacteroidaceae . These taxa are positively correlated with colonic mucin‐derived O ‐glycan abundance, but Bifidobacterium longum subsp. infantis cannot release or consume mucin glycans. Colonization with B. infantis reduced the abundance of mucin degrading taxa and reduced mucin degradation, suggesting that colonization of infants by B. infantis EVC001 may help maintain gut barrier function.